Review of the genus Falsotrachystola Breuning, 1950 (Coleoptera: Cerambycidae: Lamiinae: Morimopsini) - Huang, Gui-Qiang; Li, Song (Zootaxa, 2019)
A taxonomic review of the genus Falsotrachystola Breuning, 1950 is presented. A new species, Falsotrachystola dongi sp. nov., is described from Yunnan, southwest China. A redescription and discussion on elytral spot variation of Falsotrachystola asidiformis (Pic, 1915) are provided. Falsotrachystola is redescribed and a key to known species is presented.